Dickinson's Fascicles : A Spectrum of Possibilities - Crumbley, Paul, 1952-; Heginbotham, Eleanor Elson (Book collections on Project MUSE., 2014)
"In this volume, a number of senior and emerging Dickinson scholars raise their disparate voices with a particular set of theoretical premises, each selecting specific fascicles for close inspection. The result is the first practical, balanced, common ground for studying Dickinson's poetry in her own context"--